Synthesis and Studies of O-substituted Derivatives of Benzophenone Oxime - Mehta, Deepika; K. Baregama, Latif; Talesara, G.L. (Asian Journal of Chemistry, 2010)
In the present work, the synthesis of O-phthalimidoxyalkyl benzophenone oxime (IV) and O-(2,3-bis-phthalimidoxy) propylbenzophenone oxime (IX) are reported. These compounds contain two and three substituted amino-oxy groups respectively.